Penggunaan Media Game Online Melalui ProProfs untuk Meningkatkan Literasi Digital Siswa di SMP Negeri 1 Gangga - Siti Nurkhasanah (Jurnal Paedagogy, 2022)
This study aims to describe the use of online game media through ProProfs to improve the Digital Literacy of students at SMPN 1 Gangga. This research method uses classroom action research which is carried out in 2 cycles with the research subjects being class IX.1 students, totaling 20 students. The data collection techniques used in this study were observation, questionnaires and documentation. While the data analysis technique used descriptive analysis. The results of this study indicate that the use of online game media through ProProfs can improve the digital literacy of class IX.1 students of SMP Negeri 1 Gangga in the subject of static electricity for the 2021/2022 academic year. In addition, online game media through ProProfs is easy and practical in making and playing games, so that it makes students happy to play them and becomes a solution for using cellphones more effectively in learning.